Browning, Barbara. Samba: Resistence in Motion. Indianapolis, Indiana University Press, 1955. 190p; Guillemoprieto, Alma.Samba. New York, Columbia University Press, 1994. 244p; Hess, David. Samba in the Night. New York, Columbia University Press, 1994. 20 - MacAdams, Alison J. (Afro-Ásia, 1997)
.